2017
DOI: 10.1103/physrevlett.119.197205
|View full text |Cite
|
Sign up to set email alerts
|

Direct Imaging of a Zero-Field Target Skyrmion and Its Polarity Switch in a Chiral Magnetic Nanodisk

Abstract: A target Skyrmion is a flux-closed spin texture that has twofold degeneracy and is promising as a binary state in next generation universal memories. Although its formation in nanopatterned chiral magnets has been predicted, its observation has remained challenging. Here, we use off-axis electron holography to record images of target Skyrmions in a 160-nm-diameter nanodisk of the chiral magnet FeGe. We compare experimental measurements with numerical simulations, demonstrate switching between two stable degene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
151
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 194 publications
(162 citation statements)
references
References 36 publications
(65 reference statements)
11
151
0
Order By: Relevance
“…Similar phenomenon in three-dimensional multilayer magnetic system was reported theoretically [28] and experimentally [29][30][31]. In the structure called threedimensional skyrmion, Bloch-like skyrmions are in the middle of the film and Néel-like skyrmions are at the top and bottom surface of the film.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Similar phenomenon in three-dimensional multilayer magnetic system was reported theoretically [28] and experimentally [29][30][31]. In the structure called threedimensional skyrmion, Bloch-like skyrmions are in the middle of the film and Néel-like skyrmions are at the top and bottom surface of the film.…”
Section: Resultssupporting
confidence: 81%
“…In the structure called threedimensional skyrmion, Bloch-like skyrmions are in the middle of the film and Néel-like skyrmions are at the top and bottom surface of the film. This structure has been observed in Fe/Gd multiplayers [29], FeGe nanodisk [30], and bulk Cu2OSeO [31]. The composite only including top layer and bottom layer of the three-dimensional skyrmion is called Néel caps.…”
Section: Resultsmentioning
confidence: 79%
“…FeGe is one of the most widely studied chiral magnets that host magnetic skyrmions. Nanostructures made of FeGe, such as the wedge-shaped nanostripe [44], nanodisks [45,46] and nanowires [47], have been experimentally fabricated. Here we consider using chiral magnet FeGe with mesh size of´2 nm 2 nm 2 nm .…”
Section: Model and Methodsmentioning
confidence: 99%
“…Advances, particularly in interfacial Dzyaloshinskii-Moriya (DM) interactions, 10 have largely overcome the challenges associated with room-temperature stability. 4,11 Few approaches have been demonstrated that can stabilize skyrmions at zero applied magnetic field, but include rapid quenching, 8,12 pulsed electrical currents, 13 geometric confinement, 14,15 or pinning the skyrmions with nanostructures 16,17 . These approaches place restrictions on the skyrmion system, limiting both fundamental research and eventual device architectures.…”
Section: Introductionmentioning
confidence: 99%